Pendampingan Masyarakat dalam Peningkatan Kapasitas Manajemen Desa Wisata Berbasis Potensi Pertanian di Desa Cepoko, Gunungpati, Semarang - Suwarti, Suwarti; Aryaningtyas, Aurilia Triani; Hadi, Syamsul (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program was designed to strengthen the capacity of residents in Cepoko Village, Gunungpati District, Semarang City, to manage agricultural resources as part of a village-based tourism initiative. The program employed a participatory mentoring approach, combining training in village tourism management with hands-on simulation of agricultural tourism practices. A total of 32 participants, including farmers, small business owners, and tourism village administrators, actively engaged in the activities. The outcomes revealed a notable enhancement in participants’ understanding of village tourism concepts, strategies for leveraging agricultural potential as tourist attractions, and digital marketing techniques to promote such offerings. The average knowledge score improved substantially, rising from 3.2 to 4.4 on a five-point scale. In addition, the community collaboratively developed an educational agricultural tourism package, reflecting their ability to apply newly acquired skills in practical planning. This activity illustrates that structured capacity-building programs, combining theoretical training with technical mentoring, can empower communities to manage local resources more independently, improve their tourism management capabilities, and support the long-term sustainability of village-based tourism initiatives.